Representasi Nilai-Nilai Pendidikan Karakter dalam Cerpen “Gus Jakfar” Karya KH A. Mustofa Bisri: Kajian Sosiologi Sastra - Sani, Rizky Mutiara; Septiana, Hespi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research focuses on finding the values ​​of character education in the short story entitled “Gus Jakfar” by KH A. Mustofa Bisri through a sociological study of literature. The use of sociological literary studies is intended to analyze social interactions in short stories which produce exemplary values ​​in the form of character education. The method used is descriptive qualitative (QD) with data collection techniques using library research, where data is obtained from literature in the form of short stories, articles and books. Next, the data was analyzed using the Miles and Huberman technique through three stages, namely "reduction, data presentation, and conclusions." The results obtained from this research found four values ​​of character education, including: religious, curious, friendly/communicative, and social care. In detail, there are three data on the value of religious character education in short stories, two data on the value of character education on curiosity, one data on the value of friendly/communicative character education, and one data on the value of character education in the form of social care.